2010
DOI: 10.1116/1.3336466
|View full text |Cite
|
Sign up to set email alerts
|

Photon- and electron-stimulated desorption from laboratory models of interstellar ice grains

Abstract: The nonthermal desorption of water from ice films induced by photon and low energy electron irradiation has been studied under conditions mimicking those found in dense interstellar clouds. Water desorption following photon irradiation at 250 nm relies on the presence of an absorbing species within the H2O ice, in this case benzene. Desorption cross sections are obtained and used to derive first order rate coefficients for the desorption processes. Kinetic modeling has been used to compare the efficiencies of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(47 citation statements)
references
References 45 publications
2
45
0
Order By: Relevance
“…21,32,38 The data and results presented in this work come as a fortuitous addition to that story in the light of a more thorough review of our data. At this exposure, C 6 H 6 is present as small islands dispersed over the European Spectrometry Systems) with a homemade line-of-sight tube facing the front of the substrate upon which the molecular film is deposited.…”
Section: Experimental Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…21,32,38 The data and results presented in this work come as a fortuitous addition to that story in the light of a more thorough review of our data. At this exposure, C 6 H 6 is present as small islands dispersed over the European Spectrometry Systems) with a homemade line-of-sight tube facing the front of the substrate upon which the molecular film is deposited.…”
Section: Experimental Methodsmentioning
confidence: 94%
“…38,42 This would imply that electron-promoted desorption, initiated by cosmic ray interactions in icy grains, could be the primary non-thermal desorption mechanism in cold, dense regions in the ISM. Kimmel and co-workers have thoroughly investigated the chemistry occurring in H 2 O ices deposited on Pt(111) upon irradiation with low energy electrons (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…The mother cluster for each ion can be deduced from the contour pattern which differs from ion to ion. The ion of 16 amu is not O + but 4 CH + because it is observed without water, at the left end of Fig. 5,a, and not observed from pure water (Fig.…”
Section: Water and Methane Coadsorbed On Solid Nementioning
confidence: 99%
“…Though these assignments are bold enough, and in addition, the cluster sizes were not exactly determined at this time, it was revealed that a water molecule plays crucial roles in the process. Firstly, one water molecule is essential for the desorption of the ions investigated here except the case of 4 CH + from the isolated CH 4 molecule. Even for the case of 5 CH + and 2 3 C H , + those are likely produced from two adjacent methane molecules, the addition of one water molecule to the cluster is absolutely essential for the desorption of these species.…”
Section: Water and Methane Coadsorbed On Solid Nementioning
confidence: 99%
See 1 more Smart Citation